PENGEMBANGAN MEDIA PROMOSI KESEHATAN TENTANG KESELAMATAN BERKENDARA SEPEDA MOTOR PADA SISWA SMA - Tino Oktario Yosendha; Sri Widati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
The Safety riding by motorcycle is important, especially for student in senior high school. The save of ride is needed because many student of senior high school use motorcycle to school. There are many cases of motorcycle accidents involve by student in senior high school, because the psychology of those who are still unstable and unwary. These research aims to make safety drive health promotion that’s fi ts in SMA Budi Sejati Surabaya. This research using cross sectional research design. The fi rst draft give pre test using questionnaire, than created some prototype and conducted testing of prototype used sampling students. This sample of population are 40 students and can be through by 32 students. Based on the result showed most responden are woman. The average 16–18 years. Most of the respondents have a good knowledge, attitude, motivation, and action. In addition the most responden have vulnerability feels to motorcycle accident. The media health promotion used poster about the  importance of having drivers licence while driving by motorcycle and social media facebook.Keywords: safety riding, driving licence, Senior High School